Project SMARTER As an Intervention towards Intensifying Action Research Competencies of Basic Education Teachers - Cuarto, Polemer (JPAIR Multidisciplinary Research, 2019)
In the era of educational reforms, action research becomes highly relevant especially in basic education as this gives the teachers and the school leaders the opportunity to revisit and improve their educational practice. These explanatory sequential mixed methods study sought to investigate the effectiveness of Project SMARTER in intensifying the action research competencies of basic education teachers. Forty basic education teacher-participants (n=40) were subjected to Project SMARTER’s ten-day training intervention. Participants were pretested prior to the intervention to determine their entry knowledge on action research and were administered posttest to determine the knowledge gained through the intervention. Quantitative results revealed that participants performed significantly better from introductory to intermediate level of action research knowledge before and after the Project SMARTER intervention. To further validate the results, a qualitative phase where eight basic education teachers (n=8) were interviewed regarding their views and experiences as participants of the Project SMARTER. The phenomenological inquiry yielded three essential themes: ready to act: becoming action researchers, armed to teach: becoming teachers of research and trained to train: becoming research trainers. These essential themes signified how the project had impacted the participants as teacher-researchers, research teachers and trainers. Implications and recommendations are provided for higher education institutions, concerned government institutions as well as project implementers to consider to make project initiatives like Project SMARTER successful and sustainable.